The Effects of the Information Society on Spatial Development – Hungarian Case Study - Szépvölgyi, Ákos (Discussion Papers, 2012)
The research is targeted at assessing the spatial im¬pacts of the information society and exploring the special features of the differ¬ent levels of settlement network and of the spatial organization system. The author is starting from the assumption that individual settlements and spatial units react in different ways to these processes and these differences de¬termine their long-term development perspectives as well. He supposes that the position of areas undergoing different processes of socio-economic development has been changed by the impacts of the emerging information society. The author aims to carry out an integrated social, eco¬nomic and technological analysis on those special features of information society - as a social development paradigm - that are relevant to spatial processes. Research objectives were set up as follows: 1. The exploration of the characteristic features of the information society as a social development paradigm through an evaluation of the Hungarian and international literature. 2. Performing a complex definitive analysis on the social impacts of information society. This process includes a detailed survey of core-periphery relations and of the characteristic features of the nodes of development. 3. Finally, the author tries to answer the question what determines the adaptive skills of the different regions whilst identifying the major differences between the adaptive skills of regions with differing socio-economic background. The paper can be divided into two major parts. The first part explains the theoretical concepts and the socio-economic impacts of the information society through the survey of international (preferably English-American and German) literature. The second part contains some empirical results.